Symmetry detection in 3D chain coded discrete curves and trees. Issue 4 (April 2015) - Aguilar, Wendy; Bribiesca, Ernesto
Abstract Symmetry detection in 2D and 3D shapes has been a classical problem in computer vision, computational geometry, and pattern recognition. One of the reasons of this interest, is because symmetry is related to the balance and harmony, and in most cases it is considered like a beautiful proportion. In this paper we present different methods to detect mirror and rotational symmetries in 2D and 3D open and closed curves, and in trees represented by means of the orthogonal direction change chain code. These methods detect both global and local symmetries. They can also detect the number and position of the axes of symmetry. They are simple, easy to implement and fast to execute.